Acid-Catalyzed Reactions of Epoxides for Atmospheric Nanoparticle Growth - Xu, W.; Gomez-Hernandez, M.; Guo, S.; Secrest, J.; Marrero-Ortiz, W.; Zhang, A. L.; Zhang, R. Y. (Journal of the American Chemical SocietyJournal of the American Chemical SocietyJournal of the American Chemical Society, 2014)
Although new particle formation accounts for about 50% of the global aerosol production in the troposphere, the chemical species and mechanism responsible for the growth of freshly nucleated nanoparticles remain largely uncertain. Here we show large size growth when sulfuric acid nanoparticles of 4-20 nm are exposed to epoxide vapors, dependent on the particle size and relative humidity. Composition analysis of the nanoparticles after epoxide exposure reveals the presence of high molecular weight organosulfates and polymers, indicating the occurrence of acid-catalyzed reactions of epoxides. Our results suggest that epoxides play an important role in the growth of atmospheric newly nucleated nanoparticles, considering their large formation yields from photochemical oxidation of biogenic volatile organic compounds.
Keywords: alpha-pinene oxide; gas-phase; heterogeneous reactions; isoprene; kinetics; organosulfates; particle formation; relevant; secondary organic aerosol; sulfuric-acid